Molecular insight of flow property for gas-water mixture (CO2/CH4-H2O) in shale organic matrix. (15th March 2021) - Zhang, Lu; Li, Qibin; Liu, Chao; Liu, Yang; Cai, Shouyin; Wang, Shukun; Cheng, Qinglin
Abstract: Gas-water two-phase flow mechanism of CO2 /CH4 in moist nanoporous media is significant in carbon capture and storage (CCS) and enhanced oil and gas recovery (EOR) technology. However, in untraditional oil and gas exploitation, the flow property of CO2 /CH4 -H2 O mixtures are neglected in shale organic nanopores under reservoir conditions. In this work, molecular dynamic simulation combined with a theoretical model is performed to investigate two-phase flow characteristics of CH4 /CO2 -H2 O mixtures in shale organic nano-slits. From the density profile of gas-water mixtures in shale organic nano-slits, we find that water molecules prefer to form water clusters at the surface and center region to replace CH4 molecules of the adsorption layer (AL) and CO2 molecules of the bulk-free layer (BL), respectively. Based on the results of MD simulations, an analytical theoretical slip model is established to quantitatively characterize the effective viscosity and slip length of CH4 /CO2 -H2 O binary mixtures systems, which can be integrated into the macro framework to mimic the flow property of gas-water two-phase in shale and predict the apparent gas permeability in moist shale. Particularly, although the viscous flux of CO2 decreased with the increase of gas water mole percent (GWP) values and the slippage flux appears largely unaffected, the variation of total flux for CO2 has been small. Taking into account the influence mechanisms of H2 O molecule among the gas-water (CH4 /CO2 -H2 O) two-phase mixtures in shale organic nano-slits, CO2 displacement and fracturing technology may provide a productivity improvement avenue for shale gas.